Clandestine Philosophy : New Studieson Subversive Manuscrips in Early Modern Europe, 1620-1823 - Laursen, John Christian; Jacob, Margaret C., 1943-; Paganini, Gianni, 1950- (Book collections on Project MUSE., 2020)
Clandestine philosophical manuscripts, made up of forbidden works including erotic texts, political pamphlets, satires of court life, forbidden religious texts, and books about the occult, had an avid readership in the seventeenth and eighteenth centuries, becoming objects of historical research by the twentieth century. The purveyors of the clandestine could be found in the Dutch Republic, Switzerland, Denmark, Spain, and not least in Paris or London. Despite the heavy risks, including prison, the circulation of these manuscripts was a prosperous venture.After Ira Wade's pioneering contribution (1938), Clandestine Philosophy is the first work in English entirely focused on the philosophical clandestine manuscripts that preceded and accompanied the birth of the Enlightenment. Topics from philosophy, political and religious thought, and moral and sexual behaviour are addressed by contemporary authors working in both America and Europe. These manuscripts shed light on the birth of pornography and provide an important avenue for investigating philosophical, religious, political, and social critique.